The Miracle Tree: Manfaat Kelor Terhadap Kesehatan Masyarakat - Riza Adrianoor Saputra; Untung Santoso; Tuti Heiriyani; Jumar Jumar; Rabiatul Wahdah; Nursyam Andi Syarifuddin; Komala Aminda Putri; Alda Navira; Noor Aisyah (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2021)
Moringa oleifera is a type of plant that has many benefits. Moringa leaves are very well consumed by humans with a variety of processed products. This Community Service aims to open people's insight, knowledge, and skills about the benefits of Moringa leaves for healts, as well as provide business opportunities for farming communities who are interested in cultivating Moringa plants to increase their income. The method used in community service is in the form of counseling. The results of this activity have provided knowledge to the community, especially farmers in the Landasan Ulin Barat Village about the benefits of Moringa leaves for health. This community service is expected to be carried out in a sustainable manner, so that the counseling that has been given can be put into practice in real terms, thus providing benefits for the people of the West Landasan Ulin Village.